(untitled) (ALPHA. Journal of Arts, Literature and Philosophy, 2019)
This article studies the fundamental aspects of Dussel’s critique of the formal model of hegemony developed by Laclau. In this context, a concept of popular hegemony tied to the centrality of the reproduction of life as a normative criterion in politics is proposed, as well as an argument against the abstract decisionism of the populist theory of Laclau. The text also offers –as suggested by Castro-Gomez’s reading– a critique of Dussel’s ideas from a post-foundationalist perspective, which leads to questioning the very idea of an unconditional universal. Finally, we conclude by positing a critique of some of the theoretical viewpoints shared by both authors, identifying the limitations of the very concept of hegemony.